Zasada ostrożnej wyceny w usługach długoterminowych - Kasperowicz, Anna (Rule of Conservatism Valuation in Long-Term Services, 2005)
The rule of careful valuation has an important role in long-term services valuation. The problem of careful valuation in this kind of services exists on two levels. First - the usage of this rule can affect the choice of the method of valuation of unfinished services on the day balance sheet is shown (which affect the size of financial statement of the company). Second - in the case of choosing the method of advance work statement, establishing profits and costs should take place with respecting that rule (not over pricing established profit and under pricing established costs). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 69-78